2017
DOI: 10.1093/gbe/evx168
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Difficult Nodes in the Placental Mammal Tree with Expanded Taxon Sampling and Thousands of Ultraconserved Elements

Abstract: The phylogeny of eutherian mammals contains some of the most recalcitrant nodes in the tetrapod tree of life. We combined comprehensive taxon and character sampling to explore three of the most debated interordinal relationships among placental mammals. We performed in silico extraction of ultraconserved element loci from 72 published genomes and invitro enrichment and sequencing of ultraconserved elements from 28 additional mammals, resulting in alignments of 3,787 loci. We analyzed these data using concatena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
110
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(133 citation statements)
references
References 89 publications
22
110
1
Order By: Relevance
“…10. The development of partitioned support measures for distance-based coalescence methods (STAR, STEAC, NJ-ST, ASTRID: Liu et al, 2009b, Liu andYu, 2011;Vachaspati and Warnow, 2015) should be a priority to make sense of conflicting relationships favored by different phylogenomic coalescence methods (e.g., Esselstyn et al, 2017;Liu et al, 2017). Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…10. The development of partitioned support measures for distance-based coalescence methods (STAR, STEAC, NJ-ST, ASTRID: Liu et al, 2009b, Liu andYu, 2011;Vachaspati and Warnow, 2015) should be a priority to make sense of conflicting relationships favored by different phylogenomic coalescence methods (e.g., Esselstyn et al, 2017;Liu et al, 2017). Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…For birds and mammals, aligned reads were not available, so we 148 downloaded raw reads and followed the procedures taken by the previous authors to 149 create our aligned matrices. In the case of the mammal dataset (Esselstyn et al 2017), 150…”
Section: Genomic Characterization Of Uces Across the Tree Of Life 107mentioning
confidence: 99%
“…The first UCEs were identified by Bejerano et al (2004) in the human genome and have been shown to be conserved in mammals, birds, and even ray-finned fish. Thanks to their large-scale sequence conservation, UCEs are particularly well-suited for sequence capture experiments and have become popular for phylogenomic reconstruction of diverse animals groups (Guschanski et al 2013;Blaimer et al 2015;Esselstyn, Oliveros, Swanson, & Faircloth 2017). Initially restricted to a few vertebrate groups such as mammals ) and birds (McCormack et al 2013a), new UCE probe sets have been designed to target thousands of loci in arthropods such as hymenopterans (Blaimer et al 2015;Branstetter et al 2017a;Faircloth, Branstetter, White, & Brady 2015), coleopterans (Baca, Alexander, Gustafson, & Short 2017), and arachnids (Starrett et al 2017).…”
Section: Introductionmentioning
confidence: 99%